2010
DOI: 10.1111/j.1542-4758.2009.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulse contour‐derived cardiac output in hemodialysis patients

Abstract: Reliable methods for cardiac output determination are essential for studying the pathophysiology of intradialytic hypotension. Use of the current gold standard, the Transonic monitor, requires an arteriovenous fistula. We wished to verify the accuracy of a method based on finger pulse contour analysis, namely the Finometer monitor (FNM) for further use on patients dialyzing on a central vascular catheter. Fifty simultaneous cardiac output measurements were obtained during hemodialysis sessions in 25 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…However, it should be pointed out that this device has already been tested against intra‐arterial BP in hypertensive patients and has also been cited in several publications on dialysis patients with consistent results . In fact, one study found that the absolute cardiac output values reported by Finometer were unreliable . As our focus was the variation of each hemodynamic variable from pre‐ to post‐ HD instead of the absolute values, we have judged our method trustworthy.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, it should be pointed out that this device has already been tested against intra‐arterial BP in hypertensive patients and has also been cited in several publications on dialysis patients with consistent results . In fact, one study found that the absolute cardiac output values reported by Finometer were unreliable . As our focus was the variation of each hemodynamic variable from pre‐ to post‐ HD instead of the absolute values, we have judged our method trustworthy.…”
Section: Discussionmentioning
confidence: 73%
“…[16][17][18][19] In fact, one study found that the absolute cardiac output values reported by Finometer were unreliable. 20 As our focus was the variation of each hemodynamic variable from pre-to post-HD instead of the absolute values, we have judged our method trustworthy.…”
Section: Figurementioning
confidence: 99%
“…The only other study to address this question in hemodialysis patients was performed by Cordtz and Ladefoged . These investigators looked at 25 hemodialysis sessions in 25 patients, who underwent continuous monitoring with the Finometer, plus ultrasound dilution measurements at baseline and mid‐dialysis, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous literature, the difference between measurements was expressed both as an absolute value, and as a percentage of the mean of each measurement pair . One way analysis of variance ( ANOVA ) was used to look for significant differences in agreement between patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation